Workforce planning and training in Obstetrics and Gynaecology across Europe: A survey of national trainee societies. (July 2017) - Aabakke, Anna J.M.; Kristufkova, Alexandra; Boyon, Charlotte; Bune, Laurids T.; Van de Venne, Maud
Abstract: Objective(s): To describe the infrastructural differences in training in Obstetrics and Gynaecology (ObGyn) across Europe. Study design: Descriptive web-based survey of 31 national ObGyn trainee societies representing the 30 member countries of the European Network of Trainees in Obstetrics and Gynaecology. Answers were verified in a telephone interview and only countries which had completed the telephone interview were included in the final analysis. Results: The final analysis included 28 of 31 societies representing 27 countries (response rate 90%). The median formal duration of training was 5 years (range 4–7). There were mandatory requirements in addition to medical school graduation before specialisation could be started in 20 (71%) countries. The job opportunities after completion of training varied and included academic fellowships (n = 21 [75%]), clinical fellowships/junior consultancy (n = 21 [75%]), consultancy (n = 11 [40%]), and private practice (n = 23 [82%)]. Training and working as a specialist abroad was uncommon (≤20% in 21 [78%] and 26 [96%] countries respectively). Exams during ObGyn training were offered in 24 (85%) countries. Unemployment after completion of training was rare (<5% in 26 [93%] countries). Assessment of ObGyn specialists took place in 20 (71%) countries. Conclusion(s): The study illustrates that there are organisational variations in ObGyn training in Europe; A) The requirements to obtain a training post vary causing differences in the qualifications of trainees starting training. B) The duration of training varies. And C) newly trained specialists carry varying levels of responsibility. The results suggest that the content, organisation, and outcome of training differ across Europe. Differences due to political, social and cultural reasons are expected. However, further harmonisation of training across Europe still seems desirable in order to improve women's healthcare and facilitate the mobility of ObGyn trainees and specialists across Europe. There are currently several European initiatives, however, national and local measures are essential for training to improve.